The Influence of Emotional Intelligence, Self-Efficacy, and Independence in Learning with Moderating Variables Teacher's Leadership to Improve Mathematics Learning Outcomes - Umniyyati, Fiyya; Ellianawati, Ellianawati; Sumartiningsih, Sri (Jurnal Penelitian Pendidikan, 2025)
This study is based on the low mathematics achievement scores in fractions obtained by students and previous research findings that show inconsistent results regarding the relationship between emotional intelligence, self-efficacy, learning independence, and learning outcomes. Learning outcomes are influenced by both internal and external factors. The internal factors include emotional intelligence, self-efficacy, and learning independence, while the external factor is the role of the teacher leadership. The purpose of this study is to examine the effect of emotional intelligence, self-efficacy, and learning independence on students' learning outcomes and to test the effect of emotional intelligence, self-efficacy, and learning independence on mathematics achievement in fractions through the role of the teacher leadership as a moderating variable. The population in this study consists of fourth-grade students from 4 elementary schools in Pangkah sub-district that have a teacher leadership in their institution, with a sample size of 100 respondents using purposive sampling. Data collection was carried out by distributing questionnaires and documentation. The data analysis technique used is moderation regression analysis with a significance level of 5%. The results of the study show that emotional intelligence has a positive and significant effect on mathematics learning outcomes, with a t-value of 3.302 and p = 0.001, which is smaller than 0.05. Self-confidence also has a positive and significant effect on mathematics learning outcomes, with a t-value of 3.268 and p = 0.002. Since p < 0.05, learning independence has a positive and significant effect on learning outcomes with a t-value of 2.096 and p = 0.039. The role of the teacher leadership has a positive effect on learning outcomes, with a t-value of 2.572 and p = 0.012, which is smaller than 0.05. The results of the moderation regression analysis show that emotional intelligence has a positive and significant effect on mathematics achievement in fractions through the moderating variable of the teacher leadership with a t-value of 2.880 and p = 0.005, p < 0.05. self-efficacy also affects mathematics learning outcomes through the teacher's leadership role as a moderating variable with a t-value of 3.028 and p = 0.003, and learning independence affects mathematics learning outcomes through the teacher’s leadership role as a moderating variable with a t-value of 2.496 and p = 0.014, p < 0.05. Based on the research findings, it can be concluded that emotional intelligence, self-efficacy, and learning independence have a positive and significant direct effect on mathematics learning outcomes in fractions. Furthermore, with the role of the teacher as a change agent, emotional intelligence, self-confidence, and learning independence significantly influence mathematics learning outcomes in fractions.